Piety over Protest: Cognitive Liberation and Deflected Collective Action in Central India. (2nd September 2016) - Hasnain, Aseem
Abstract: Cognitive liberation is often treated in the social movements literature as a mediating factor through which political opportunities and mobilizing structures generate protest. This paper unpacks multiple dimensions of cognitive liberation and finds that they may operate in tension with one another. Building on scholarship that focuses on subjective factors in social movements, the paper examines the case of the Korku, an oppressed indigenous community in central India, who choose not to protest despite the presence of several dimensions of cognitive liberation. Rather than engage in collective political action, the Korku's grievances are deflected toward depoliticized religious goals. The Korku seek communal improvement through Hindu piety in a context of the Hindutva cultural-nationalist ideology, rather than protest against the encroachment of this ideology on their community.